2015
DOI: 10.1093/toxsci/kfv081
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-30 Protects Against Carbon Tetrachloride-induced Liver Fibrosis by Attenuating Transforming Growth Factor Beta Signaling in Hepatic Stellate Cells

Abstract: Transforming growth factor beta (TGF-β) is crucial for transdifferentiation of hepatic stellate cells (HSCs) and the blunting of TGF-β signaling in HSCs can effectively prevent liver fibrosis. Krüppel-like factor 11 (KLF11) is an early response transcription factor that potentiates TGF-β/Smad signaling by suppressing the transcription of inhibitory Smad7. Using a mouse model of carbon tetrachloride (CCl4)-induced liver fibrosis, we observed significant upregulation of KLF11 in the activated HSCs during liver f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…In our previous study, we found that miR-30 blunted TGF-β/Smad signaling in HSCs by targeting KLF11, which suppressed the transcription of inhibitory Smad7 in TGF-β/Smad pathway 31 . Here, we further revealed that the inhibition of KLF11 by miR-30 resulted in the upregulation of Smad7 in hepatocytes (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In our previous study, we found that miR-30 blunted TGF-β/Smad signaling in HSCs by targeting KLF11, which suppressed the transcription of inhibitory Smad7 in TGF-β/Smad pathway 31 . Here, we further revealed that the inhibition of KLF11 by miR-30 resulted in the upregulation of Smad7 in hepatocytes (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…We previously found that hepatic miR-30s decreased in the fibrotic liver and HSC-specific upregulation of miR-30 prevented liver fibrosis 31 . Here, we examined miR-30s expressions in the hepatocyte after CCl 4 treatment and found that they decreased about 1~4-fold (Supplementary Figure S2A).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Several other studies have indicated that miR‐30c is significantly reduced in a model of pathological left ventricular hypertrophy 7, 8. MiR‐30c regulates the production of ECM in TGF‐β‐dependent liver fibrosis 9, 56. MiR‐30c reduces renal fibrosis and improves renal function in diabetic nephropathy by targeting connective tissue growth factor (CTGF) 10.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research shows that various intracellular signal transduction pathways are involved in regulating the progression of activation of HSCs and hepatic fibrosis (He and Dai 2015;Pinzani and Marra 2001). Transforming growth factor-β (TGF-β) signaling pathway is the most common and important pathway of those in the development of hepatic fibrosis (Tu et al 2014(Tu et al , 2015. During the classical Smad-dependent pathway of TGF-β signaling, TGF-β and TGF-β receptors often trigger the phosphorylation of Smad2 and Smad3.…”
Section: Introductionmentioning
confidence: 99%